Dynamics and Determinants of Market Integration of Green, Clean, Dirty Energy Investments and Conventional Stock Indices - Liu, Xin; Bouri, Elie; Jalkh, Naji (Frontiers in Environmental Science, 2021)
We examine market integration across and clean and green investments, crude oil, and conventional stock indices covering technology stocks, and US and European stocks. Using daily data covering the period December 1, 2008 - October 8, 2020, we first apply the dynamic equicorrelation (DECO) model and make inferences regarding the time-varying level of market integration. Then, we use several regression models and uncover the driving factors of market integration under lower and upper quantiles of the distribution of the equicorrelation. The results show that return equicorrelation varies with time and is shaped by the COVID19 outbreak. Various uncertainty measures are the main drivers of market integration, especially at high levels of market integration. During the COVID-19 outbreak period, the US Dollar index, the term spread, and the Chinese stock market index have significantly increased market integration.